Поетика пасторального ландшафту в німецькому романі XVII століття - Пастушенко, Л. (Інститут літератури ім. Т.Г.Шевченка НАН України, 2009)
На материале анализа романной пасторали «частного содержания» изучаются топологические и регионально специфические элементы буколического локуса. Показано, что немецкие писатели вписывают «устойчивый, вечный духовный пейзаж» (Л.Баткин) в комплекс социокультурных представлений о национально характерном, специфически германском неаркадийском пространстве, одновременно подвергая ревизии и значительно реформируя европейский опыт жанра. The material of the novel pastoral with “private contents” is used for maintaining the analysis of topological and regionally marked elements of the bucolic locus. It’s shown up that German authors insert “stable, eternal spiritual landscape” (L.Batkin) into the complex of social and cultural views concerning the national character, specific German non-Arcadian space, the European experience of the genre being revised and reformed considerably.